Metacognitive Reading Strategies Employed by Grade Nine Male and Female Students: A Study in Addis Ababa Secondary Schools - Berhe, Elfinesh; G/Mariam, Alamirew (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
This study examined the level and preference of metacognitive reading strategies used by Grade 9 students at Ula-dula General Secondary School in Ethiopia. 130 students (59 males and 71 females) participated in the study and filled out the questionnaire. Six of them took part in the interviews. The data was collected using the Metacognitive Awareness Reading Strategy Inventory (MARSI) and a semi-structured interview. SPSS (Statistical Package for the Social Sciences Version 24) was used to analyze the quantitative data, while thematic analysis was employed for the qualitative data. The results indicated that students used the metacognitive reading strategies moderately, with an average mean score of 2.8. However, individual students' use of the strategies showed that 40% of the students used the strategies at a low level, 26.2% at a high level, and 33.8% at a medium level. The problem-solving strategies were used most frequently, followed by global and support strategies in second and third place, respectively. Problem-solving and global strategies were utilized moderately, while support strategies were employed at a lower level. The results of an independent sample t-test revealed no significant correlation between the gender of the students and their usage of the strategies. In summary, while the average result showed that students, as a whole, used the strategies moderately, the majority of individual students were found to use them at a low level. The qualitative data provided further evidence to support the quantitative findings. The result suggests that the students' low level of reading proficiency might have been due to a lack of awareness and inappropriate utilization of reading strategies.